Contesting the Crisis - CUPE, the CAW, and Third Way Neoliberalism in Ontario from 2003-2013 - Watson, James (My University, 2020)
This research uses Gramscian claims about culture and resistance to assess the radical potential of trade unions under neoliberalism. Using a comparative case study, this research examines the implications of chosen strategies of resistance deployed by the leading public- and private-sector unions (Canadian Union of Public Employees – CUPE, and Canadian Auto Workers – CAW, respectively) during the pre- and post-Great Recession phases of the McGuinty Liberal government in Ontario. The key contributions of this work are relevant for the fields of political sociology, political economy, and labour studies. In the field of political sociology, this work finds that contesting hegemonic governance strategies requires both a resistance against opportunities for integration and incorporation and the articulation of and organization around radical and non-sectionalist (systemic) alternatives. Second, this work demonstrates how political economic considerations are contested both structurally and culturally through both organizational-institutional and ideological-symbolic interventions. Finally, this research holds implications for strategies of union renewal by analyzing the capacities and limitations of certain strategic interventions in the lead-up and aftermath of a large-scale economic crisis.